Dakota/Lakota Math Connections: an epistemological framework for teaching and learning mathematics with Indigenous communities and students - Luecke, Danny; Sanders, David (Frontiers in Education, 2023)
Tribal colleges/universities have and continue to seek out connections between the local heritage and culture and the mainstream education content. In math, calls for culture to be more integrated into the classroom have been met with epistemological challenges as well as a dearth of math and local culture resources. The Dakota/Lakota Math Connections research project addresses both of these challenges. This article will specifically share on the collaborative development, pilot, evaluation, and confirmation of an epistemological framework for curriculum development in both the math and language classrooms at Sitting Bull College. Following an Indigenous research paradigm focusing on relationality and relational accountability, the co-authors gathered a group of tribal college math instructors, Lakota language immersion teachers, and fluent elders. Altogether they experienced, evaluated, and confirmed the Dakota/Lakota Math Connections framework as a path for teaching and learning mathematics with Indigenous communities and students. Using an Indigenous research paradigm led to circular, reciprocal research questions for this article: In what ways, if any, did the framework impact the participants? In what ways, if any, did the participants influence the framework? The framework includes four major components (Western Math, Dakota/Lakota Math, the English language, and the Dakota/Lakota language) and the intersections among each component. The framework builds from the assumptions that language is intimately tied with culture and identity and that higher order mathematical thinking is embedded within Dakota/Lakota language and culture. This is based on the assumption that all cultures "do" math. The framework asserts that math fluency and Dakota/Lakota language fluency can grow together. The Dakota/Lakota Math Connections framework lays an epistemological pathway for Dakota/Lakota students to see their culture, identity, and language in the math curriculum as well as for math instructors to honor the call to connect the math classroom with the local heritage and culture.